1977
DOI: 10.1192/bjp.130.6.592
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Obsessive-Compulsive Neurosis with History of Childhood Autism

Abstract: A young man was followed-up over three years who had severe obsessive-compulsive rituals and ruminations, interpersonal deficits, complicating depression and a history of childhood autism. Intensive behavioural treatment was given in an operant framework, with exposure in vivo, modelling, response prevention and social skills training. Compulsive rituals improved markedly and lastingly, but ruminations and social defects persisted. When intercurrent depression occurred dothiepin facilitated behavioural treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…There were seven case reports, four small N experiments, two uncontrolled group designs, and two RCTs treating anxiety in ASD including OCD symptoms. Thirteen studies evaluated interventions for children and adolescents (<18 years) (El-Ghoroury and Krackow 2011; Handen et al 1984;Kuhn et al 2009;Lehmkuhl et al 2008;Lindly et al 1977;Marchant et al 1974;Ooi et al 2008;Reaven and Hepburn 2003;Rodriguez et al 2012;Rooney et al 2011;Sze and Wood 2009;Sigafoos et al 2009;Sofronoff et al 2005;Wood et al 2009) and one evaluated treatment for adults (Russell et al 2008). Seven reported standardized ASD diagnostic assessments (Lehmkuhl et al 2008;Ooi et al 2008;Reaven and Hepburn 2003;Russell et al 2008;Sigafoos et al 2009;Sofronoff et al 2005;Sze and Wood 2009) and seven reported OCD diagnoses (El-Ghoroury and Krackow 2011; Lehmkuhl et al 2008;Reaven and Hepburn 2003;Rooney et al 2011;Russell et al 2008;Sze and Wood 2009;Wood et al 2009), of which three reported standardized diagnostic assessments (Rooney et al 2011;Sze and Wood 2009;Wood et al 2009).…”
Section: Empirically Supported Treatmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were seven case reports, four small N experiments, two uncontrolled group designs, and two RCTs treating anxiety in ASD including OCD symptoms. Thirteen studies evaluated interventions for children and adolescents (<18 years) (El-Ghoroury and Krackow 2011; Handen et al 1984;Kuhn et al 2009;Lehmkuhl et al 2008;Lindly et al 1977;Marchant et al 1974;Ooi et al 2008;Reaven and Hepburn 2003;Rodriguez et al 2012;Rooney et al 2011;Sze and Wood 2009;Sigafoos et al 2009;Sofronoff et al 2005;Wood et al 2009) and one evaluated treatment for adults (Russell et al 2008). Seven reported standardized ASD diagnostic assessments (Lehmkuhl et al 2008;Ooi et al 2008;Reaven and Hepburn 2003;Russell et al 2008;Sigafoos et al 2009;Sofronoff et al 2005;Sze and Wood 2009) and seven reported OCD diagnoses (El-Ghoroury and Krackow 2011; Lehmkuhl et al 2008;Reaven and Hepburn 2003;Rooney et al 2011;Russell et al 2008;Sze and Wood 2009;Wood et al 2009), of which three reported standardized diagnostic assessments (Rooney et al 2011;Sze and Wood 2009;Wood et al 2009).…”
Section: Empirically Supported Treatmentsmentioning
confidence: 99%
“…Two other nonexperimental case studies describe the treatment of OCD using ERP with other techniques (Lindly et al 1977;Rooney et al 2011). Lindly et al (1977) used ERP with a token economy, modeling, social skills training, and dothiepin to reduce touching and looking rituals of a 17-year old with autism.…”
Section: Behavior Analysis and Behavior Modificationmentioning
confidence: 99%
See 3 more Smart Citations